Evidence for transitional stages in the evolution of euglenid group II introns and twintrons in the Monomorphina aenigmatica plastid genome. - Jean-François Pombert; Erick R James; Jan Janouškovec; Patrick J Keeling (PLoS ONE, 2012)
Photosynthetic euglenids acquired their plastid by secondary endosymbiosis of a prasinophyte-like green alga. But unlike its prasinophyte counterparts, the plastid genome of the euglenid Euglena gracilis is riddled with introns that interrupt almost every protein-encoding gene. The atypical group II introns and twintrons (introns-within-introns) found in the E. gracilis plastid have been hypothesized to have been acquired late in the evolution of euglenids, implying that massive numbers of introns may be lacking in other taxa. This late emergence was recently corroborated by the plastid genome sequences of the two basal euglenids, Eutreptiella gymnastica and Eutreptia viridis, which were found to contain fewer introns.To gain further insights into the proliferation of introns in euglenid plastids, we have characterized the complete plastid genome sequence of Monomorphina aenigmatica, a freshwater species occupying an intermediate phylogenetic position between early and late branching euglenids. The M. aenigmatica UTEX 1284 plastid genome (74,746 bp, 70.6% A+T, 87 genes) contains 53 intron insertion sites, of which 41 were found to be shared with other euglenids including 12 of the 15 twintron insertion sites reported in E. gracilis.The pattern of insertion sites suggests an ongoing but uneven process of intron gain in the lineage, with perhaps a minimum of two bursts of rapid intron proliferation. We also identified several sites that represent intermediates in the process of twintron evolution, where the external intron is in place, but not the internal one, offering a glimpse into how these convoluted molecular contraptions originate.